Acceleration of Ovarian Maturation in the Female Mud Crab With RNA Interference of the Vitellogenesis-Inhibiting Hormone (VIH) - Duangprom, Supawadee; Saetan, Jirawat; Phanaksri, Teva; Songkoomkrong, Sineenart; Surinlert, Piyaporn; Tamtin, Montakan; Sobhon, Prasert; Kornthong, Napamanee (Frontiers in Marine Science, 2022)
In the present study, double strand RNA technology (dsRNA) was used to inhibit transcripts of vitellogenesis-inhibiting hormone (VIH) that mainly synthesized and secreted from the central nervous system in Scylla olivacea females. The results presented in this study clearly demonstrate the potential dsRNA-VIH was highly effective to inhibit VIH in the eyestalks of females injected with dsRNA-VIH on the 3rd, 7th and 14th day, respectively. The dsRNA-VIH injections were performed at 14-day intervals, a single dsRNA dose of 0.6 µg/ gram body weight was enough to suppress VIH expression until 14th day after injection. The dsRNA-VIH injection significantly increased gonad-somatic index (GSI) and hemolymph vitellin level at day 14 and 28 when compared with control groups. The histological observation found that the number of oocyte step 4 in dsRNA-VIH group was significantly higher than that of the control group. Also, dsRNA-VIH has stimulatory function on other reproduction-related genes such as the Scyol-PGES and Scyol-ESULT that both genes gradually increased their expressions in brain and ventral nerve cord. In conclusion, the silence of VIH gene could reduce the production of VIH from eyestalk and brain that affected other downstream genes related to ovarian maturation in the mud crab.